Sendo f (x)=3x-1 e g (f (x))=3x-3 determine a função g (x)
Soluções para a tarefa
Respondido por
0
Boa noite!
![g(x)=ax+b\\f(x)=3x-1\\g(f(x))=af(x)+b=a(3x-1)+b=3ax-a+b=3x-3\\3a=3\\a=1\\-a+b=-3\\-1+b=-3\\b=-2\\g(x)=x-2 g(x)=ax+b\\f(x)=3x-1\\g(f(x))=af(x)+b=a(3x-1)+b=3ax-a+b=3x-3\\3a=3\\a=1\\-a+b=-3\\-1+b=-3\\b=-2\\g(x)=x-2](https://tex.z-dn.net/?f=g%28x%29%3Dax%2Bb%5C%5Cf%28x%29%3D3x-1%5C%5Cg%28f%28x%29%29%3Daf%28x%29%2Bb%3Da%283x-1%29%2Bb%3D3ax-a%2Bb%3D3x-3%5C%5C3a%3D3%5C%5Ca%3D1%5C%5C-a%2Bb%3D-3%5C%5C-1%2Bb%3D-3%5C%5Cb%3D-2%5C%5Cg%28x%29%3Dx-2)
Espero ter ajudado!
Espero ter ajudado!
Perguntas interessantes
História,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás